Prospects of Halal Food Industry: Contribution to Sharia Economic Growth - Hanin Nur Laili; Khairil Anwar (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
Indonesia's active involvement as a country with a Muslim majority population in halal regulation and standardization began in the late 1980s, which also shows the development of the food industry and the sharia economy in Indonesia. The purpose of this study is to show the contribution of the halal food industry to the growth of the sharia economy in Indonesia. The method used was qualitative, and data collection was conducted through a literature review of both primary and secondary data sources. The results of this study indicate that increased consumption of halal food shows a positive correlation with economic growth in Indonesia. The halal food industry plays an essential role in promoting the Islamic economy. In Indonesia, the halal food and beverage industry has become one of the main sectors with the largest contribution to economic growth. The increasing demand for halal production, particularly in the food sector, from Muslim consumers who are increasingly aware of the halal status of the products they consume will drive the growth of the Islamic economy. The trend toward halal products, particularly in the halal food sector, also serves as a benchmark for non-Muslim communities, who view halal products as representing standards of cleanliness and food quality. Indonesia has great potential to become a global leader in the halal industry. By properly implementing the sharia economic master plan, Indonesia can leverage the potential of the halal food industry to strengthen the sharia economy as a whole.